OPTIMAL EXTRACTION PARAMETERS OF THEABROWNIN FROM SICHUAN DARK TEA - Zou, Yao; Qi, Guinian; Xu, Tian; Cheng, Shen-xiang; Liu, Ting-ting; Huang, Ya-fang (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Sichuan Dark Tea is a popular beverage with hypolipidemic and lifting greasy properties in the minorityneighborhoods of Sichuan and Tibet regions. The theabrownin, an important pigment of dark tea, has been proven for the role of thehypolipidemic property in Sichuan Dark Tea. The objective of the study investigated the extraction process of theabrownin.Materials and Methods: Theabrownin was extracted from Sichuan Dark Tea with water and organic solvents. The quadraticregression orthogonally rotational combinational design experiment was performed to obtain the optimal extraction parameters.Results: The extraction yield of theabrownin was significantly influenced by both water extraction temperature and solid-liquid ratio,and the contribution of these factors on theabrownin yield was as follows: water temperature﹥solid-liquid ratio﹥organic solventtemperature. Moreover, the polynomial regression model established could predict the experimental value accurately.Conclusion: The optimum extraction process of theabrownin from Sichuan Dark Tea was established, which water temperature at65.69-77.88℃, organic solvent temperature at 13.65-17.48℃ and a solid-liquid ratio of 1:43.58-1:50.75(g/mL).